Haemato-Biochemical Profile And Immunity To 12th Passaged Eimeria Spp. Oocysts In Fowl (Gallus Domesticus) (Applied Biological Research, 2016)
The present study was conducted in 24 fowls (Gallus domesticus) randomly  divided into 3 groups. Group I was kept as negative control. Group II,  positive control, was induced with 5000 field strain of sporulated Eimeria spp. oocysts and group III induced with 5000 passages strain of Eimeria spp.  oocysts. On day 21, group II and III were challenged with homologous  virulent strain of Eimeria spp. Blood and faecal samples were collected at  days 26, 31 and 36. One bird from each group was sacrificed on day 28 for  lesion scores. All haematological parameter differed significantly, except  basophils. Serum transaminases, glucose, body weight and oocyts g-1 showed significant change. Heavy lesion score appeared in group II. High stimulation  index value was found on day 31 and distinct band of precipitation was  observed in group III. The passaged oocysts feeding might be useful in  protecting mixed Eimeria species infection in fowls.
Keywords: Fowl; Eimeria spp; Hemato-biochemical; attenuated strain; immunity